Sexually transmitted infections among pre-exposure prophylaxis users in a Swedish multi-centre cohort - Herder, Tobias ; 0000-0002-8504-4031; Månsson, Fredrik; Tunbäck, Petra; Sanner, Karin; Gisslén, Magnus; Fridenström, Ester; Dawar, Minna; Strömdahl, Susanne (European Journal of Public Health, 2025)
An additional upsurge in bacterial STIs has been observed in Sweden following HIV pre-exposure prophylaxis (PrEP) implementation. From a prevention perspective, it is of relevance to optimize testing strategies within PrEP programmes to identify those most at risk. An open retrospective longitudinal observational cohort study was performed at three STI clinics in Uppsala, Gothenburg, and Malmö. A questionnaire and journal data regarding STI were collected from a sample of 199 MSM enrolled in the PrEP programmes and providing informed consent. Incident bacterial STIs during follow-up were analyzed with descriptive statistics, Poisson regression, and Cox regression. Median follow-up time was 632 days. A total of 270 gonorrhoea or chlamydia infections were recorded during PrEP follow-up, compared to 194 cases in the 2-year period prior to enrolment, giving an incidence rate ratio (IRR) of 1.56 (CI 95% 1.30-1.89). The testing frequency increased by 75% (IRR 1.69, CI 95% 1.60-1.90). For diagnoses of active syphilis, the increase was 108% (IRR 2.08. CI 95% 1.04-4.06), compared with a 5-year period preceding enrolment. The hazard ratio of time (days) until a first STI after PrEP initiation was 2.87 (CI 95% 1.72-4.80) for those having had a STI prior to PrEP initiation and 2.06 (CI 95% 1.03-4.13) for those reporting experience of group sex in the past year compared with those who had not. STI prior to PrEP initiation and group sex were associated with STI after initiation of PrEP, factors that could be considered if needing prioritizing the frequency of STI screening.
© The Author(s) 2025. Published by Oxford University Press on behalf of the European Public Health Association.
Keywords: gonococcal infection; syphilis; follow-up; men who have sex with men; pre-exposure prophylaxis